An Analysis of Sales Budget in Increasing Profit at Dadang Shop in Sukamakmur Village - Asti Dwy Rahayu; Yun Fitriano; Rina Trisna Yanti (Journal of Indonesian Management, 2021)
This study aims to analyze the sales budget in increasing profits at Dadang Shop in Sukamakmur Village of Marga Sakti Sebelat Sub-District in North Bengkulu Regency. The data collection technique is the most strategic step in the study, because the main objective of the study is to obtain data. The results of this study indicate that the Sales Budget at Dadang Shop in Sukamakmur Village is quite effective in increasing the price. From the 2019 sales budget using the Least Square method, which is IDR 154,219,538,011, realized IDR 4,270,649,857, above a budget of IDR 4,116,429,948,989 by an increase of the number of customers and an increase of the number of products sold. Meanwhile, from the sales budget for January 2019 using the sales budget calculation of IDR 574,016,114.91, this increase is due to the number of customers and the number of products being sold continues to increase every month.